1973
DOI: 10.1079/pns19730003
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of processing and storage on the nutritive value of milk and milk products

Abstract: Milk is an excellent food and its composition makes it an ideal medium for the growth of micro-organisms, including pathogens, which may be present in raw milk, either as a result of infections in the cow or pathogens introduced adventitiously during subsequent handling. T o ensure a safe product of good keeping quality it is necessary to control microbial contamination. This is normally effected by some form of heat-treatment or by the conversion of liquid milk into a dry powder or a moist product, such as ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…According to Resnawati, lactose is an energy source for the growth of LAB in fermented milk, which in the next process, will act as a producer of acid levels in fermented milk. The longer fermented milk is stored, the energy source, in the form of lactose, will be overhauled by LAB, and there will be an increase in the total acidity of the fermented milk [22].…”
Section: Total Titrated Acidmentioning
confidence: 99%
“…According to Resnawati, lactose is an energy source for the growth of LAB in fermented milk, which in the next process, will act as a producer of acid levels in fermented milk. The longer fermented milk is stored, the energy source, in the form of lactose, will be overhauled by LAB, and there will be an increase in the total acidity of the fermented milk [22].…”
Section: Total Titrated Acidmentioning
confidence: 99%
“…The browning reaction proceeds more rapidly at water activities of 0.3-0.5 than at higher ones, and in the presence of pentoses or hexoses than of disaccharides (Wolf et al, 1982). Dworschak (1980) cites the work of Rolls and Porter (1973) which indicated that UHT (130-150°C for 1 set) heating of milk produced no detectable loss in available lysine or methionine. Conversely, Kisza et al (1967) found methionine in milk to be reduced from 3.26 to 2.64% by pasteurization.…”
Section: Amino Acid Analysismentioning
confidence: 99%
“…Initial quality of milk with respect to microbial load and the extent of deterioration before processing can have an adverse effect on the stored products (Ispen and Hansen 1988). Milk foods containing high levels of protein, unsaturated fats and reducing sugars tend to undergo browning reactions, resulting in rancidity of products (Rolls and Porter 1973). Sensory quality of the products decreases mainly as a result of off flavor caused by oxidation of milk fat (Badings and Neeter 1980).…”
Section: Introductionmentioning
confidence: 99%